Análise textual: construção das relações e das representações sociais em produção de alunos dos anos finais do ensino fundamental e do ensino médio - Fortunato, Marina Pinheiro (2011)
We conducted our research with students from the eighth grade of elementary school and third year of High School to the Public of the State of São Paulo. We begin the analysis with the research studies Fairclough (2001) that addresses a three-dimensional conception of discourse by stating that the three-dimensional method of discourse analysis is the speech and any instance of discursive practice that should be seen as both a linguistic text, oral and writing, a discourse practice (text production and interpretation) and sociocultural practice. Fairclough (2001) considers his work through a relationship between discourse and society, addressing the discursive practice through the interpretation of the relationship established not only with the orders of discourse and discursive practices that already exist, but also to social structures, ideologies and relationships existing power in these discourses. Other reflections are present in this work, among them, Pedro (1997), Dijk (2008) who also have certain concepts from the theories of discourse analysis in a critical dimension. The importance of studying these theories is that we can understand the power relations and ideologies from school premises, observing the students productions. What we want to prove that the factors are also present in argumentative student texts and their social representations are in discourse. Thus, we get the understanding for our analysis on textual linguistics to evaluate argumentative markers in the productions and the influence of ideological constraints present in the processes of textual production